Dabigatran must be used carefully: literature review and recommendations for management of adverse events - Lin S; Wang Y; Zhang L; Guan W (Dove Medical Press, 2019)
Shan Lin,* Yan Wang,* Lei Zhang, Wei GuanDepartment of Respiratory Medicine, Qinghai University Affiliated Hospital, Xining 810001, People’s Republic of China*These authors contributed equally to this workAbstract: Atrial fibrillation increases the risk of stroke and death. The vitamin-K antagonist warfarin is recommended for patients with atrial fibrillation, but vitamin-K antagonists are cumbersome to use. Therefore, an effective, safe and convenient new anticoagulant is needed. Dabigatran acts by inhibiting free and fibrin-bound thrombin directly. It is an oral anticoagulant that was approved by the US Food and Drug Administration. The oral anticoagulant dabigatran has been used increasingly due to its good tolerance, predictable pharmacokinetics, effective anticoagulant effects, and absence of requirement of coagulation monitoring. However, an increasing prevalence of adverse events has been reported, some of them quite serious. Therefore, we searched and reviewed the literature on dabigatran with regard to adverse events, and proposed solutions to prevent and reduce the chance of adverse events occurring.Keywords: adverse events, dabigatran, allergic reactions, bleeding, esophageal injury